2020
DOI: 10.1177/0148558x20916338
|View full text |Cite
|
Sign up to set email alerts
|

Depositor Characteristics and the Performance of Islamic Banks

Abstract: We investigate the reasons for the growing demand for Islamic banking internationally, and examine the relative economic performance of Islamic banks compared with conventional banks in managing their capital buffers and liquidity. Using data for the period 2000–2012 for 104 Islamic and 619 conventional listed and non-listed banks spread across 22 countries with both these types of banks, and using standard statistical methodology for archival data analysis, we find that religious, political, and socio-legal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
(44 reference statements)
0
7
0
4
Order By: Relevance
“…Islamic financial institutions provide a variety of interest-free products; therefore, they are involved with their customers’ business transactions by sharing profits and losses (Alharthi, 2016). The Islamic banking system acts as a supervisor of depositors’ resources and can use them to generate profit for its customers (Visser, 2019; AlAbbad et al , 2020). Unlike Islamic banks, conventional banks mainly borrow, lend and charge interest on such funds (Alharthi, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Islamic financial institutions provide a variety of interest-free products; therefore, they are involved with their customers’ business transactions by sharing profits and losses (Alharthi, 2016). The Islamic banking system acts as a supervisor of depositors’ resources and can use them to generate profit for its customers (Visser, 2019; AlAbbad et al , 2020). Unlike Islamic banks, conventional banks mainly borrow, lend and charge interest on such funds (Alharthi, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Sementara kinerja keuangan bank syariah secara keseluruhan mungkin tertinggal dari bank konvensional, pertumbuhn mereka hanya dapat dikaitkan dengan fakta bahwa mereka melayani kebutuhan spesifik dari sektor masyarakat tertentu. Oleh karena itu, tidak tepat jika hanya menggunakan kinerja keuangan standar untuk mengevaluasinya atau menjelaskan pertumbuhan dan keberhasilannya (Abbad et al, 2021). Selain itu, penelitian ini juga mampu memberikan wawasan tentang penilaian kesehatan bank, dimana penelitian ini sangat penting dalam meletakkan dasar regulator untuk menekankan manajemen risiko di Industri perbankan.…”
Section: Pendahuluanunclassified
“…(2019) analyzed the financial performance of Islamic and conventional banks in Malaysia within the scope of a dual setting arrangement in the Malaysian financial industry where performance evaluation of both types of banks relies on ratio analyses which include return on equity, return on assets, earnings per share and debt ratio from 2012 to 2016 using t -test and correlation analysis where the results indicate that the Malaysian conventional banks performed better than Islamic banks which calls that Islamic banks should further improve their performance to become more competitive in the current environment for the financial industry. Al-Abbad et al (2020) investigate the reasons depositor characteristics and the performance of Islamic banks using data from 2000 to 2012 for 104 Islamic and 619 conventional listed and non-listed banks spread across 22 countries using standard statistical methodology for archival data analysis where the findings revealed that Islamic banks maintain significantly higher liquidity buffers than their conventional counterparts. Al-Hawatmeh (2020) undertakes a study on the possibility of using the BSC performance evaluation system in evaluating the performance of internal control in Jordanian commercial banks where the researcher designed a questionnaire and distributed it to managers, internal managers and employees in Jordanian commercial banks and out of the 450 questionnaires distributed, recovered 370 with adoption to be valid for statistical analysis purposes (345) at a rate of 77%.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Empirically, it is in line with Choong et al (2012), Hamedian (2013), Hazman et al (2018), Basri et al (2019) and Sulub et al (2019), all in Malaysia. Moreover, Usman and Khan (2012) in Pakistan, Yahaya and Lamidi (2015) in Nigeria, Kamarudin et al (2017) in selected Southeast Asian countries, Al-Alawi (2018) in Bahrain, Al-Abbad et al (2020) across 22 countries and Al-Hawatmeh (2020) in Jordanian. Nonetheless, it is in contrast with the findings of Ullah (2014) in Bangladesh, Abofaied (2017) and Filfilan (2020) in the GCC countries which found that the performance of Islamic banks is not encouraging.…”
Section: Summary Of Statisticsmentioning
confidence: 99%
See 1 more Smart Citation